Service Quality, MDR, Ease of Use, QRIS User Satisfaction in Surakarta City Micro Businesses - Mualifah, Iklilah Egil; Muharrami, Rais Sani (Universitas Muhammadiyah Surakarta, 2024)
The purpose of this research is to examine the effect of service quality, MDR, and ease of use on QRIS user satisfaction at micro businesses in Surakarta City. This research uses quantitative methods. The population in this study were micro businesses as QRIS merchants in Surakarta City. Sampling was carried out using random sampling technique, the sample size was 100 respondents. Data collection was carried out by distributing questionnaires directly to respondents. The results of this study state that: (1) service quality with t-Statistic results 2.953 > 1.984, and a probability value of 0.004 < 0.05, meaning that service quality has a positive and significant effect on QRIS user satisfaction in Surakarta City micro businesses. (2) MDR with a t-Statistic result of 6.093 > 1.984, and a probability value of 0.000 < 0.05, meaning that MDR has a positive and significant effect on QRIS user satisfaction in Surakarta City micro businesses. (3) Ease of use with t-Statistic results 2.798 > 1.984, and a probability value of 0.006 < 0.05, meaning that ease of use has a positive and significant effect on QRIS user satisfaction in micro business actors in Surakarta City. The coefficient of determination test shows that variable (X) can affect variable (Y) by 48.5%. Data processing stages with Eviews 12 software include validity and reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis, coefficient of determination (R2), T test (Partial).